Negative Regulation of miR‐375 by Interleukin‐10 Enhances Bone Marrow‐Derived Progenitor Cell‐Mediated Myocardial Repair and Function After Myocardial Infarction. (25th August 2015) - Garikipati, Venkata Naga Srikanth; Krishnamurthy, Prasanna; Verma, Suresh Kumar; Khan, Mohsin; Abramova, Tatiana; Mackie, Alexander R.; Qin, Gangjian; Benedict, Cynthia; Nickoloff, Emily; Johnson, Jennifer; Gao, Ehre; Losordo, Douglas W.; et al.
Abstract: Poor survival and function of transplanted cells in ischemic and inflamed myocardium likely compromises the functional benefit of stem cell‐based therapies. We have earlier reported that co‐administration of interleukin (IL)−10 and BMPAC enhances cell survival and improves left ventricular (LV) functions after acute myocardial infarction (MI) in mice. We hypothesized that IL‐10 regulates microRNA‐375 (miR‐375) signaling in BMPACs to enhance their survival and function in ischemic myocardium after MI and attenuates left ventricular dysfunction after MI. miR‐375 expression is significantly upregulated in BMPACs upon exposure to inflammatory/hypoxic stimulus and also after MI. IL‐10 knockout mice display significantly elevated miR‐375 levels. We report that ex vivo miR‐375 knockdown in BMPAC before transplantation in the ischemic myocardium after MI significantly improve the survival and retention of transplanted BMPACs and also BMPAC‐mediated post‐infarct repair, neovascularization, and LV functions. Our in vitro studies revealed that knockdown of miR‐375‐enhanced BMPAC proliferation and tube formation and inhibited apoptosis; over expression of miR‐375 in BMPAC had opposite effects. Mechanistically, miR‐375 negatively regulated 3‐phosphoinositide‐dependent protein kinase‐1 (PDK‐1) expression and PDK‐1‐mediated activation of PI3kinase/AKT signaling. Interestingly, BMPAC isolated from IL‐10‐deficient mice showed elevated basal levels of miR‐375 and exhibited functional deficiencies, which were partly rescued by miR‐375 knockdown, enhancing BMPAC function in vitro and in vivo. Taken together, our studies suggest that miR‐375 is negatively associated with BMPAC function and survival and IL‐10‐mediated repression of miR‐375 enhances BMPAC survival and function. Stem Cells 2015;33:3519–3529